British Virgin Islands : Financial Sector Assessment Program Update; Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2010)
This paper focuses on financial regulatory policies and stability. The British Virgin Islands (BVI) provides administrative, audit, and legal services to international business companies, which is another key component of the economy. Developments in the financial sector and regulatory framework warrant an update of the assessment conducted under the IMF's Offshore Financial Center (OFC) program. Financial Services Commission Act (FSCA) provides the Financial Services Commission (FSC) with a wide array of specific regulatory, supervisory, and enforcement powers. The banking system has been insulated from global financial shocks. Many critical elements develop a robust and proportionate crisis management framework.